THE STUDY OF SPEECH ACT OF CONSENT IN URDU - Muskan Masood; Saba Nousheen; Maha Ghazanfar (International Journal of Contemporary Issues in Social Sciences, 2024)
Language plays a crucial role in the development of human intellectuality, social skills, and emotion, making it an essential communication tool. Language is a human, non-instinctive method for communicating ideas, emotions, and desires through voluntarily produced symbols (Hartman and Stork, 1973:124 cited in Kaswan and Suprijadi, 2011:9). This study attempts to highlight the speech act of consent in Urdu language. According to John Lyons (1968) Language is studied scientifically in linguistics. In this research the researchers have used the types of consent given by Chambliss, D.F and Schutt, R.K. (2018) in making sense of the social world. Consent is an approval to do something or permission for something to happen. This research investigates all types of speech act of consent in Urdu in both formal and in formal situations. The main purpose is to tell which types of consent are used in formal situations, and which are used in informal situations. For this purpose, the researchers have collected survey forms by doing convenience sampling. This study combines data through qualitative research. The analysis is presented in description. A discourse completion task (DCT) is used to collect data. The researchers concluded that the speech act of consent is used very randomly in both formal and informal situations. This is the conclusion the researcher came upon after all the surveys that are done. This research will be significant for students, teachers and future researchers may also use it as a reference in their work. The particular demands and expectations of the circumstance in which consent is being sought will determine which option is best.